If a , b & c are the roots of the polynomial x 3 − 2 x 2 + 3 x + 1
Find the value of a 5 + b 5 + c 5 − ( a 4 + b 4 + c 4 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you so much. Your solutions have literally been as good as a teacher teaching.
I cant understand why newton sums ques. Are so highly overrated on brilliant ... ...
So many questions of the same Type out there. Even I use newtons sums for all of them
The same way i did. Sir, that's a very good solution.
great solution
Newton's sums are great!!
Log in to reply
Finally learnt Newton Sum. Pretty interesting and very easy. ..
S o m e t h i n g f r o m f u n d a m e n t a l s . B y V i e t a ′ s : − a + b + c = 2 . a b + b c + c a = 3 . a b c = − 1 . a 2 + b 2 + c 2 = − 2 . . . . . . . . . . . . . . . . . . . . . . . . . . a 2 + b 2 + c 2 = ( a + b + c ) 2 − 2 ( a b + b c + c a ) = − 2 . a 2 b 2 + b 2 c 2 + c 2 a 2 = 1 3 . . . . . . . . . . . . . . . . . a 2 b 2 + b 2 c 2 + c 2 a 2 = ( a b + b c + c a ) 2 − 2 a b c ( a + b + c ) = 1 3 . a 4 + b 4 + c 4 = − 2 2 . . . . . . . . . . . . . . . . . . . . . . . a 4 + b 4 + c 4 = ( a 2 + b 2 + c 2 ) 2 − 2 ( a 2 b 2 + b 2 c 2 + c 2 a 2 ) = − 2 2 a 5 + b 5 + c 5 = − 3 . . . . . . . . . . . . . . . . . . . . . . . . . a 5 + b 5 + c 5 = ( a + b + c ) ( a 4 + b 4 + c 4 ) − { a ( b 4 + c 4 c ) + b ( c 4 + a 4 ) + c ( a 4 + b 4 ) } . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . = ( a + b + c ) ( a 4 + b 4 + c 4 ) − { a b ( a 3 + b 3 ) + b c ( b 3 + c 3 ) + c a ( c 3 + a 3 ) } . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . = ( a + b + c ) ( a 4 + b 4 + c 4 ) − { a b ( − 1 3 − c 3 ) + b c ( − 1 3 − a 3 ) + c a ( − 1 3 − b 3 ) } . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . = ( a + b + c ) ( a 4 + b 4 + c 4 ) − { − 1 3 ( a b + b c + c a ) − a b c ( c 2 + a 2 + b 2 ) } . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . ( 2 ) ( − 2 2 ) − { − 1 3 ( 3 ) − ( − 1 ) ( − 2 ) } = − 3 ∴ a 5 + b 5 + c 5 − ( a 4 + b 4 + c 4 ) = − 3 − ( − 2 2 ) = 1 9 .
we use newton sums. http://www.artofproblemsolving.com/Wiki/index.php/Newton%27s_Sums
Dablo Ashu ko😂.....chew seong cheong already made use of it.
Problem Loading...
Note Loading...
Set Loading...
The problem can be solved by Newton's Sums method.
Let P n = a n + b n + c n , where n = 1 , 2 , 3 . . . and:
S 1 = a + b + c = 2 S 2 = a b + b c + c a = 3 S 3 = a b c = − 1 .
Then, P n are given as follows:
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ P 1 = S 1 P 2 = S 1 P 1 − 2 S 2 P 3 = S 1 P 2 − S 2 P 1 + 3 S 3 P 4 = S 1 P 3 − S 2 P 2 + S 3 P 1 P 5 = S 1 P 4 − S 2 P 3 + S 3 P 2 = 2 ( 2 ) − 2 ( 3 ) = 2 ( − 2 ) − 3 ( 2 ) + 3 ( − 1 ) = 2 ( − 1 3 ) − 3 ( − 2 ) − 1 ( 2 ) = 2 ( − 2 2 ) − 3 ( − 1 3 ) − 1 ( − 2 ) = 2 = − 2 = − 1 3 = − 2 2 = − 3
Therefore,
a 5 + b 5 + c 5 − ( a 4 + b 4 + c 4 ) = P 5 − P 4 = − 3 − ( − 2 2 ) = 1 9